The Amendment of the Religious Registration Law and Its Impact on Freedom of Religion in the Slovak Republic - Havelková, Mária (Public Governance, Administration and Finances Law Review, 2018)
Church registration represents a legitimate instrument of surveillance over religious groups. In the Slovak Republic, registered churches are funded directly out of the State budget and dispose of a wide range of other financial, as well as non-financial benefits. Slovakia has recently tightened up the already strict registration criterion of a number of supporters. According to the currently effective legislation, a church or religious society applying for registration must provide evidence of having over 50,000 members. The main aim of this article is to analyse the impact of the new Slovak legislation on the freedom of religion with a focus on assessment of whether the rang of rights and duties for registered churches are the same as for not registered ones and whether this measure is in conformity with human rights standards applied in the European Union, as well as the Council of Europe.